Effects of ultrasound-assisted enzymolysis on the physicochemical properties and structure of arrowhead-derived resistant starch. (July 2021) - Liang, Qiufang; Chen, Xinxiang; Ren, Xiaofeng; Yang, Xiaoming; Raza, Husnain; Ma, Haile
Abstract: The effects of ultrasound-assisted enzymolysis on the physicochemical properties and structure of arrowhead-derived type 3 resistant starch (RS3) were investigated. Compared with the traditional enzymolysis, ultrasonic treatment significantly ( p  < 0.05) increased the resistant starch yield by 34.46%. Enzymolysis reaction kinetics revealed that ultrasound-assisted enzymolysis remarkably increased the enzymolysis rate and amylose content. After ultrasound treatment, RS3 displayed higher solubility, swelling power, transparency, and water absorption capacity. The results of particle-size distribution, differential scanning calorimetry, X-ray diffraction, Fourier transform-infrared spectroscopy, and scanning electron microscopy analyses demonstrated that RS3 prepared by ultrasound-assisted enzymolysis exhibited a larger granule size, higher crystallinity, a more ordered and stable double helix structure with increased surface roughness compared to those of RS3 prepared by traditional enzymolysis. These findings provide a theoretical background for the preparation of RS3 using an ultrasound-assisted enzymatic method and will promote the development of ultrasound chemistry in starch science and technology. Highlights: Ultrasound significantly ( p  < 0.05) increased arrowhead resistant starch 3 (RS3) yield. The introduction of ultrasound changed the physicochemical properties of RS3. The introduction of ultrasound changed the structural characteristics of RS3. Ultrasound-assisted pullulanase enzymolysis can be well used to prepare arrowhead RS3.